Pronostics Factors of Csm; Experience of Military Hospital of Rabat/Maroc about 107 Cases - Patrice Koffi, Niamien; Kouakou, Frank; Jawad, Laaguili; Cherkaoui, Mandour; Miloud, Gazzaz; Brahim, El Mostarphid (International Journal of Innovative Research in Medical Science, 2021)
Background: The surgery outcome of cervical spondylotic myelopathy (CSM) for some authors depend to the clinical signs (obesity, smoking, sex, age, patient’s activity, and the surgery delays). Nevertheless, for others authors it’s depending to the chirurgical approach (anterior or posterior or the levels number of decompression in the cervical spine). There is no consensus although some arguments prevail over to others in the literature. Our study purpose was to determine the important clinical factors predictors of surgical outcome in patients with CSM. It’s a retrospective study of 107 patients admitted to the Mohamed V hospital in Rabat over 06 years from January 2013 to December 2018 for cervical spondylotic myelopathy (CSM) operated and were followed up for 1year. Their neurological status pre and postoperative was assessed using the Japan Orthopedic Association (JOA) score and others prognostics factors such as sex, age, duration of symptoms, Cobbs angle, number of discs compressed, MODIC class signal and, (P<0.05) was statistically significant. Patients were classified into 02 groups, youngers patients in group 1 = G1 (<60 years of age; n = 70) and an elderly patients group = G2 (>/=60 years of age; n = 37). The mean age = 52.72 years [42.27-63.16], male 64.5% against 35.5% of women, a sex ratio = 2/1 in favor of men. In G1, mean age X1= 45.6 years. In G 2, mean age X2 = 61.85 years. The average delays for surgery = 11.28 months [6-18.19]. In G1 it was 10.30 months and 16.34 months in G2. The pre operatory JOA score (JOA PREO) = 9.87 +/- 2.033. JOA PREO score was 11 and 7 respectively in G1 and G2. The prevalence of MODIC (MC) = 52.23% and type 2 of MC was predominant in both groups, with p> 0.05. G1 patients underwent an ACDF in 82% and laminectomy in 18%. In G 2 laminectomy was performed in 50% and the anterior discectomy in 21.73%, corporectomy in 28.27%. After surgery, JOA score passed to severe to moderate 13.48 and 13.27 after 1year of follow-up in G1 and G2. In conclusion those factors such as sex, number of discs involved, and Cobbs angle on prognosis were not statistically significant (P>0.05) but patient’s age and duration of symptoms < 1 year predict to have more neurologic improvement (P<0.05) according to the JOA score.